Wood modification by heat treatment: a review - Esteves, Bruno (2012)
Wood heat treatment has increased significantly in the last few years and is still growing as an industrial process to improve some wood properties. The first studies on heat treatment investigated mainly equilibrium mois-ture, dimensional stability, durability and mechanical properties. Mass loss, wettability, wood color, and chemical transformations have been subsequently extensively studied, while recent works focus on quality control, modeling, and study the reasons for the improvements. This review explains the recent interest on the heat treatment of wood and synthesizes the major publications on this subject on wood properties, chemical changes, wood uses, and quality control.